KEDUDUKAN BARANG VIRTUAL MENURUT HUKUM BENDA INDONESIA YANG DIATUR DALAM KUHPERDATA BUKU KEDUA TENTANG BARANG - Yafet Febrian Valentino Tololiu; Muh Jufri Ahmad (Gapenas Publisher, 2023)
This research aims to find out about the position of virtual Property in Indonesian object law which is regulated in the second book of the Civil Code concerning objects. This is due to the existence of virtual Property themselves which only exist in the virtual world or cyber world, but virtual Property are also treated the same as objects in general. This research was conducted using the Normative Juridical method, namely an approach from the point of view of law or applicable laws and regulations. Data from this study were collected by examining various kinds of formal legal principles such as laws, literature which are theoretical concepts which are then linked to the issues that are the subject of discussion. The analysis was carried out using a statutory approach and a conceptual approach which were then processed and arranged systematically and the results were presented in a qualitative descriptive way. The results of this study indicate that virtual Property are intangible objects regulated in the Civil Code (KUHPerdata) because they fulfill all the elements of intangible objects, namely: an object, part of property, can be owned, has no body, in the form of rights. However, virtual Property are not in the form of rights but resemble tangible objects that do not have a physical body. Therefore, in the last element of intangible objects extensive translation is carried out, namely by expanding the meaning that the meaning of intangible objects is not limited to rights, but allows other forms as long as they fulfill the elements of objects. Based on this discussion, this study recommends the need for a more in-depth study of virtual Property based on Indonesian law, so that regulations are created that explicitly regulate virtual Property in Indonesian material law. there is, or there will be